PENGARUH SIKAP KONSUMEN TERHADAP PREFERENSI KONSUMSI DALAM UPAYA MEMBANGUN EKUITAS WISATA KULINER DI KOTA SOLO - Yustina Wuri Wulandari, Lamidi (Universitas Slamet Riyadi, 2014)
Solo is a city of tourism. Many tourism event held in Solo, which aims to create the impression (image) that Solo has a rich culture of high-value, one of which is a culinary tourism. Solo is a city that known as regional culinary like tengkleng, timlo, nasi liwet, tumpeng, and gudeg. It is attractive to foreign and domestic tourists to come at Solo. Solo government responded the situation with the place of culinary like Galabo, Ngarsopuro, Keprabon and Dapur Solo. The type of research is survey. The population of this research is consumers which take a culinary tourism in Solo. Sample of 100 people with convenience sampling technique. Data collection using questionnaires. Source of data using primary and secondary data. Analysis using Structural Equation Modeling (SEM) with AMOS. The results of hypothesis testing known that consumer attitudes positive effect on brand reliability with CR value 2,228 and p value 0,026. Positively influence consumer attitudes toward the brand intentions with CR value 2,117 and p value 0,034. Brand reliability positive influence on brand loyalty with CR value 2,220 and p value 0,026. Brand intentions positive effect on brand loyalty with CR value 2,689 and p value 0,007. Brand loyalty has positive influence on brand equity with CR value 2,142 and p value 0,032. Keywords: consumer attitudes, brand reliability, brand intentions, brand reliability, brand loyalty, brand equity